Validation Study for the Brief Measure of Quality of Life and Quality of Care: A Questionnaire for the National Random Sampling Hospital Survey. (August 2017) - Shimizu, Megumi; Fujisawa, Daisuke; Kurihara, Miho; Sato, Kazuki; Morita, Tatsuya; Kato, Masashi; Miyashita, Mitsunori
Background: To monitor quality of life (QOL) for patients with cancer in a large population-based survey, we developed a short QOL and quality-of-care (QOC) questionnaire. To determine the validity and reliability of this new questionnaire for evaluating QOL in patients with cancer. Methods: Outpatients and inpatients at National Cancer Center Hospital East were administered a questionnaire, including the following items—the short QOL and QOC questionnaire (physical distress, pain, emotional distress, walk burden, and need for help with self-care; perceived general health status; and satisfaction with medical care and treatment by doctor, communication with doctor, support by health-care staff other than doctor, care for physical symptoms such as pain, and psychological care), the Functional Assessment of Cancer Therapy—General (FACT-G), the Cancer Care Evaluation Scale (CCES) for patients, and demographic and medical data. We then readministered the short QOL and QOC questionnaire. Results: In total, 329 outpatients and 239 inpatients completed the survey (response rates: 80% and 90%, respectively). Total Cronbach α for the short QOL and QOC questionnaire was 0.83 for outpatients and 0.82 for inpatients. Items of the questionnaire correlated with cancer-specific measurements, FACT-G, and CCES. Intraclass correlation coefficients for all items of the questionnaire were 0.79 and 0.89 in each setting. Items of QOL and QOC did not correlate with each other. Conclusion: The validity and reliability of the short QOL and QOC questionnaire appear sufficient. This questionnaire enables continuous monitoring of patient QOL in large population-based surveys.